THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT DUTA VISUAL NUSANTARA TIVI TUJUH JAKARTA SELATAN - Angga Pratama (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aimed to determine the effect of work motivation and work environment on employee performance at PT Duta Visual Nusantara Tivi Tujuh, South Jakarta, either partially or simultaneously. The method used is quantitative. The method used in this research is the descriptive analysis method with a quantitative approach. This study shows that work motivation has a significant effect on employee performance with the regression equation Y = 17.134 + 0.572X1. The correlation value of 0.694 means that the two variables have a strong relationship level. The value of the coefficient of determination is 48.1%. Hypothesis test obtained t arithmetic > t table or (7.765 > 1.997). The work environment significantly affects employee performance with the regression equation Y = 14,424 + 0,642X2. The correlation value of 0,687 means that the two variables have a strong relationship level. The value of the coefficient of determination is 47.1%. Hypothesis test obtained t arithmetic > t table or (7.614 > 1.997). Work motivation and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 7,741 + 0,392X1 + 0,432X2. The correlation value of 0.804 means that the independent and dependent variables have a very strong relationship level. The value of the coefficient of determination is 64.6%, while other factors influence the remaining 35.4%. Hypothesis test obtained F arithmetic > F table value or (58.469 > 2.750).